Pendampingan Wirausaha Pupuk Organik Cair dari Urin Kelinci Melalui Teknologi Sederhana untuk Ekonomi Peternak Lokal - Mukhlison Mukhlison; Sunan Trioko; Meisya Alma Azizah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The primary goal of this Community Service Program (PKM) is to assist local farmers in utilizing rabbit urine waste—previously discarded into a value-added product in the form of liquid organic fertilizer (LOF). This innovation aims not only to enhance technical production skills but also to stimulate local economic growth through entrepreneurship based on local resources. The program involves several strategic steps: designing a simple fermentation device using a 20-liter bucket equipped with an airlock and digital thermometer; providing technical training in the LOF-making process, quality control, and hygiene standards; offering entrepreneurial mentoring in production management, financial recording, branding, and marketing; and developing local distribution networks through farmer groups and agricultural shops. The results show that partners can independently produce consistent-quality LOF, packaged in 600 ml bottles with simple labeling for commercial appeal. The program improves technical and entrepreneurial skills, increases farmers’ income, fosters cooperation, and supports sustainable agriculture through environmentally friendly waste utilization.